1997
DOI: 10.1590/s0100-879x1997000400009
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of meal-related, rhythmic and homeostatic mechanisms and the generation of thirst and drinking

Abstract: One of the primary goals of the study of thirst is to understand why drinking occurs under ad libitum or natural conditions. An appreciation of the experimental strategies applied by physiologists studying thirst from different perspectives can facilitate progress toward understanding the natural history of drinking behavior. Drinking research carried out using three separate perspectives -homeostatic, circadian rhythms, and food-associated -generates types of information about the mechanisms underlying drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The present study used a mathematically-derived meal definition (Zorrilla et al, unpublished data) that explicitly included prandial drinking (Fitzsimons and Le Magnen 1969;Kraly et al 1978;Kraly 1983;Kraly and Corneilson 1990;Rossi and Scharrer 1992;Johnson and Johnson 1997;Morgan et al 2000;Tolkamp et al 2000). The temporal distribution of post-meal intervals, the emission of the behavioral satiety sequence following judged meal termination, large stable individual differences in meal patterning, coherent factor structure, and perceived microstructural effects of a wellcharacterized anorectic (i.e.…”
Section: Meal Definitions and Prandial Drinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study used a mathematically-derived meal definition (Zorrilla et al, unpublished data) that explicitly included prandial drinking (Fitzsimons and Le Magnen 1969;Kraly et al 1978;Kraly 1983;Kraly and Corneilson 1990;Rossi and Scharrer 1992;Johnson and Johnson 1997;Morgan et al 2000;Tolkamp et al 2000). The temporal distribution of post-meal intervals, the emission of the behavioral satiety sequence following judged meal termination, large stable individual differences in meal patterning, coherent factor structure, and perceived microstructural effects of a wellcharacterized anorectic (i.e.…”
Section: Meal Definitions and Prandial Drinkingmentioning
confidence: 99%
“…Autocorrelation analysis has suggested a cutoff of 14 min between feeding events (Demaria-Pesce and Nicolaidis 1998). Finally, we recently validated a meal definition which explicitly includes prandial drinking (Fitzsimons and Le Magnen 1969;Kraly et al 1978;Kraly 1983;Kraly and Corneilson 1990;Rossi and Scharrer 1992;Johnson and Johnson 1997;Morgan et al 2000) in which the threshold meal criterion was found to be 5 min between feeding or drinking responses (Zorrilla et al, unpublished data). Under this drinking-inclusive definition, the post-meal likelihood of resuming feeding conformed to predictions of satiety (i.e., initially a very low probability that monotonically increases thereafter).…”
Section: Introductionmentioning
confidence: 99%